2016
DOI: 10.1590/1678-98652016000100006
|View full text |Cite
|
Sign up to set email alerts
|

Extrauterine growth restriction: Universal problem among premature infants

Abstract: Objective: To analyze the growth rate of premature infants in the first weeks of life and factors associated with extrauterine growth restriction. Methods: This is a cross-sectional study of 254 premature infants in a neonatal intensive care unit conducted from January 1, 2008 to December 31, 2010. Infants who died or had malformations incompatible with life were excluded. Median weight curves according to gestational age were constructed for the first four weeks of life. The Fenton growth chart calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
2
2
0
1
Order By: Relevance
“…2), the incidence was highest in moderate to late preterms compared to extremely preterm infants (79% Vs 71.4%) at univariate level. Shan et al [20] and Freitas et al [21] associated PGF with increasing gestational age which is consistent with our findings. These studies like ours included all preterms less than 37 weeks but earlier studies focused on preterm infants less than 34 weeks and could have missed the growth dynamics in older preterms.…”
Section: Discussionsupporting
confidence: 93%
“…2), the incidence was highest in moderate to late preterms compared to extremely preterm infants (79% Vs 71.4%) at univariate level. Shan et al [20] and Freitas et al [21] associated PGF with increasing gestational age which is consistent with our findings. These studies like ours included all preterms less than 37 weeks but earlier studies focused on preterm infants less than 34 weeks and could have missed the growth dynamics in older preterms.…”
Section: Discussionsupporting
confidence: 93%
“…16 A study by Lima et al observed that 54.2% of the SGA infants had EUGR at discharge considering weight and 7.4% considering HC, while only 12.3% of the AGA infants had EUGR at discharge considering weight and 4% considering HC. 22 In our study, NEC developed in 8.6% of babies in EUGR group. Incidence of NEC as per weight of baby was found to be is 3% in 500-750 grams, 3% in 750-1000 grams, 3% in 1000-1250 grams and 2% in 1250-1500 grams.…”
Section: Discussionsupporting
confidence: 48%
“…15 A Nigerian study found that babies with gestational age <32 weeks accounted for 34.2% mortalities. 16 [17][18][19] Earlier time to achieve full enteral feeds in present study may be because of strict adherence to SFR and different gestational age groups. Shukla et al, showed that by adopting the new nutritional practice guidelines there was a significant reducing trend in time to full feeds.…”
Section: Discussionmentioning
confidence: 71%